Influence of microwave power on mechanical properties of microwave-cured polyethylene/coir composites. Issue 6 (2nd June 2020) - Singh, Manoj Kumar; Zafar, Sunny
ABSTRACT: The present work deals with investigating the influence of microwave power on mechanical properties of 20 wt.% coir reinforced high-density polyethylene (HDPE) composites. Chopped coir/HDPE composites were fabricated using various microwave power levels (360 W, 540 W, 720 W and 900 W). The XRD analysis of the specimens reveals that crystallinity index in various specimens was in the range of 79.54% to 84.59%. The specimen cured at 360 W exhibited a maximum tensile strength of 29.5 ± 1.5 MPa, which is 28.26% greater than composite cured at 900 W (23 ± 1.5 MPa). Flexural strength of specimen cured at 360 W was maximum (37.74 ± 2 MPa).